Pembuatan Permen Jelly Untuk Kesegaran Dan Kesehatan Tubuh Dari Jahe Bagi Ibu PKK Desa Cinta Rakyat Kabupaten Deli Serdang Percut Sei Tuan - Safriana Safriana; Enny Fitriani; Lili Nurmaliza; Ruseni Ruseni; Ayu Diah Lestari; Hasniar Hasniar; Mella Candani; Sri Wulan Syahfitri; Syafitri Aulia (Health Community Service, 2024)
Most of the daily activities of the people in Cinta Rakyat Percut Sei Tuan Village, Deli Serdang Regency, North Sumatra Province, are still being housewives and helping their husbands with farming and fishing. This village is ± 11 km from the Indah Medan College of Health Sciences campus. Most of the women in this village are members of PKK groups and village organizations and various activities in the village, but are limited to religious and other social activities, the rest mostly stay at home. Ginger jelly candy functions to help improve body health, warm the body, relieve body aches. So it has great potential to be developed into a superior product. These production results can later be marketed through daily necessities shops, supermarkets, restaurants, or through village unit cooperatives in Deli Serdang Regency, or online.The implementation method offered to support program realization, the first stage of this activity is conducting observations and making cooperation agreements with partners. The people of Cinta Rakyat Percut Sei Tuan Village, Deli Serdang, North Sumatra, have gained an understanding of the benefits of ginger jelly candy for health, skills in how to make, package and market Ginger jelly candy using plant ingredients that are healthy, strong and easy to obtain, in a safe way. easy and simple equipment. In conclusion, the people of Cinta Rakyat Village mostly work to help their husbands farm or take part in PKK women's activities. Jelly candy can function to help improve body health, so it has the potential to make ginger jelly candy products and can be sold at public figures or supermarkets to increase family income. Ginger functions to reduce allergies, relieve digestive system disorders, relieve menstrual pain